DFT‐based direction‐of‐arrival estimation using a nested minimum redundancy array. Issue 2 (1st April 2020) - Eghbali, Yasoub; Naeiny, Mahmoud Ferdosizade
Abstract : Performance of the discrete Fourier transform (DFT)‐based direction‐of‐arrival (DoA) estimation method depends on the number of antennas. Increasing the number of antennas will improve the accuracy of DoA estimation. In this study, the authors propose a new DFT‐based DoA estimation method using a nested minimum redundancy array (NMRA). By vectorisation of the covariance matrix of the received signal of an NMRA with low number of antennas, a virtual uniform linear array with a large number of antennas can be obtained. An initial estimation of DoAs can be derived by applying the normalised centralised DFT matrix to the observations of virtual uniform linear array. By minimisation of the difference between the virtual linear array observations and their estimated values, the accuracy of DoA estimation will be improved. Simulation results show that the proposed method has better performance in comparison with the conventional ones.